2014
DOI: 10.1590/1517-86922014200301525
|View full text |Cite
|
Sign up to set email alerts
|

Força de preensão manual em atletas de judô

Abstract: RESUMOIntrodução: A força de preensão manual é a capacidade da mão em realizar tarefas, imprimir forças e segurar objetos. Dentre os diversos esportes que utilizam a força de preensão manual com predominância em sua prática, um deles é o judô, aonde a força de preensão manual é imprescindível para que o judoca consiga se impor ao adversário, pois está ligada à capacidade de realização do golpe. O objetivo deste estudo foi avaliar a força de preensão manual em atletas de judô. Métodos: O estudo contou com a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
7
0
5
Order By: Relevance
“…The Maximum Handgrip Strength (HGSMax) analysis identifies the individual's handgrip strength. It is indicated by the American Society of Hand Therapists (ASHT) and it is widely used to assess such type of strength in judokas (Lima, Kubota, Monteiro, Baldan, & Pompeu, 2014).…”
Section: Maximum Handgrip Strength Test (Hgsmax) Analysismentioning
confidence: 99%
“…The Maximum Handgrip Strength (HGSMax) analysis identifies the individual's handgrip strength. It is indicated by the American Society of Hand Therapists (ASHT) and it is widely used to assess such type of strength in judokas (Lima, Kubota, Monteiro, Baldan, & Pompeu, 2014).…”
Section: Maximum Handgrip Strength Test (Hgsmax) Analysismentioning
confidence: 99%
“…In relation to the values of handgrip strength, the athlete's experience, combined with a longer training time, seems to be associated with an increase in muscle strength when compared to the beginner and higher ranked athletes (Costa et al, 2011;Lima et al, 2014). It should be emphasized that handgrip strength tends to be higher in relation to height and body mass increase (Franchini et al, 2000), a fact observed in the winners, since these are taller, heavier and have higher values of handgrip strength than losers.…”
Section: Training Time and Morphofunctional Factorsmentioning
confidence: 99%
“…Handgrip strength is an important characteristic of the hand in different sportiness activities and information about it is relevant to develop lesion prevention´s protocols and to train strength of hand (Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The hand is one of the most important parts of the human body, distinguishing humans from other animals by peculiar grip movement, that can be by fingers flexion -the strength grip -and by approximation of thumb and second finger -the precision grip (Lima et al, 2014;Baptista et al, 2013). The hand permits to make movements that involve high levels of strength to sustain or minimal strength to manipulate objects in exercises that demand precision (Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation